Post-Operative Pain Management in Patients Undergoing Robotic Urological Surgery - Batley, Sian E. (Curr Urol, 2016)
Robotic urological surgery is being increasingly performed worldwide. The main focus currently is on the operative technique but post operative patient care is an essential part of the process to make this technique safe and successful. We present a review on multiple analgesic techniques available to prevent and treat pain specifically caused after by urological robotic surgery; this article will explain the mechanism of pain pathways involved in laparoscopic procedures and review current evidence pertaining to systemic and regional analgesia methods.